A new remarkable Isoperla species with abdominal processes from Hubei Province of Central China (Plecoptera: Perlodidae) - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2020)
A remarkable new species of Isoperla Banks, 1906, I. sextuberculata Huo & Du, sp. nov. from Hubei Province, Central China is described. The new species is distinguished by the unique paired abdominal processes on male terga 4, 7, and 8. The new species is compared to similar Isoperlinae congeners.